Polyester resin, injection molded body, polyester sheet, and polyester container - HIROKANE, TAKESHI; YOSHIMURA, YASUAKI (2015)
A polyester resin according to the present invention contains diol units and dicarboxylic acid units, wherein 50 to 95 mol% of the diol units are units derived from a pentacyclopentadecane dimethanol represented by a prescribed formula (I) and/or a pentacyclopentadecane dimethanol represented by a prescribed formula (II), 50 to 100 mol% of the dicarboxylic acid units are units derived from an aromatic dicarboxylic acid, and predetermined conditions (1) and (2) are both satisfied.